2017
DOI: 10.3748/wjg.v23.i47.8345
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ-LDLRAD3 as a biomarker in diagnosis of pancreatic cancer

Abstract: AIMTo analyze the diagnostic value of a circular RNA (circRNA), circ-LDLRAD3, in pancreatic cancer.METHODSExpression levels of circ-LDLRAD3 were tested in both cells and clinical samples; the latter included 30 paired pancreatic cancer tissues and adjacent non-tumorous tissues, 31 plasma samples from patients with pancreatic cancer, and 31 plasma samples from healthy volunteers. Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) was performed to measure expression levels of circ-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
142
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 36 publications
(41 reference statements)
0
142
0
2
Order By: Relevance
“…3 Competing endogenous RNAs (ceRNAs) compete with other RNAs for the seed region of shared miRNAs, thus modulating the activity of the miRNAs. 9,10 However, many circRNAs still need to be discovered. [4][5][6] Recently, it has been reported that abundant conserved miRNA response elements (MREs) exist in circRNAs, 7 making circRNAs a hot topic in ceRNA family research.…”
Section: Introductionmentioning
confidence: 99%
“…3 Competing endogenous RNAs (ceRNAs) compete with other RNAs for the seed region of shared miRNAs, thus modulating the activity of the miRNAs. 9,10 However, many circRNAs still need to be discovered. [4][5][6] Recently, it has been reported that abundant conserved miRNA response elements (MREs) exist in circRNAs, 7 making circRNAs a hot topic in ceRNA family research.…”
Section: Introductionmentioning
confidence: 99%
“…As was discovered by Yang et al, circLDLRAD3 was upregulated and was significantly associated with cell invasion and metastasis in PC [13]. Chen et al studied the circrna_100782 regulation through the IL6-STAT3 pathway on PC cell proliferation [14].…”
Section: Discussionmentioning
confidence: 96%
“…Among the included publications, a total of 43 articles on 64 studies were analyzed involving 10,123 subjects in Table . Of the 64 studies, five studies focused on colorectal cancer (Ji et al, ; Wang, Li, et al, ; Wang et al, ; Zhang, Yang, et al, ; Zhuo, Lin, Chen, Huang, & Hu, ), 10 on breast cancer (Lu et al, ; Yin et al, ), 22 on gastric cancer (Chen, Li, Zhao, Xiao, & Guo, ; Huang, He, Liang, Huang, & Zhu, ; Li, et al, , ; Li, Shao, et al, ; Li, Song, et al, ; Lu et al, ; Lu, Shao, Ye, Xiao, & Guo, ; Shao, Chen, et al, ; Shao, Li, et al, ; Shao, Yang, et al, ; Sun, Tang, et al, ; Tian, Chen, Li, & Xiao, ; Wei et al, ; Xie et al, ; Zhao, Chen, Li, Xiao, & Zhang, ), four on lung cancer (Li, Wang, Chen, Chen, & Jin, ; Zhu et al, ; Zong et al, ), 16 on hepatocellular carcinoma (Chen, Zhang, Lin, Song, & Wang, ; Fu et al, , ; Li et al, ; Qin et al, ; Shang et al, ; Yao et al, ; Yao et al, ; Zhang, Zhang, Lin, & Wang, ; Zhang, Zhou, et al, ; Zhang, Xu, et al, ) and seven on other cancers (Fan, Cao, Liu, Zhang, & Li, ; Lan et al, ; Li et al, ; Sun, Li, et al, ; Teng et al, ; Wang, Xue, et al, ; Yang et al, ). Moreover, three articles with 13 studies explored the diagnostic value of the combined circRNAs (Chen, Li, Zhao, et al, ; Fan et al, ; Li, Shao, et al, ) in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies found that single circRNAs yield good diagnostic performance in tissue or plasma (Shang et al, ; Sun, Tang, et al, ; Wang, Li, et al, ; Zong et al, ). Moreover, several studies provided that single circRNAs in combination with other plasma protein biomarkers such as CEA, CA‐15.3, CA‐125 and AFP possess better diagnostic performance (Huang et al, ; Prefumo, ; Yang et al, ; Yin et al, ; Zhang, Yang, et al, ). Additionally, a single circRNA combined with other circRNAs obtained also had better diagnostic accuracy (Li, Chen, et al, ; Li, Shao, et al, ; Ren & Xin, ).…”
Section: Discussionmentioning
confidence: 99%